Faktor Penghambat dan Pendukung Pemenangan Pada Pemilihan Walikota dan Wakil Walikota - Putri, Pusparani Sahran; Febriany, Febriany; Maulana, Mohammad Iqbal (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2025)
This study examines the inhibiting and supporting factors of Hidayat-Sigit’s victory in the 2015 Palu Mayoral Election using a political marketing approach based on the 4P concept (Product, Price, Place, Promotion). A qualitative descriptive study with an interpretive approach was conducted through interviews, observation, literature review, and documentation. Data were analyzed using Miles and Huberman’s interactive model, including data reduction, data presentation, and conclusion drawing. The results show that a well-planned political marketing strategy, such as forming a success team, mobilizing volunteers using an MLM approach, and leveraging Hidayat’s mass base, was a key supporting factor in their victory. Inhibiting factors include limited financial resources and the negative public perception of Sigit’s celebrity image, which affected voter trust. The study concludes that effective political marketing strategies, grounded in market research and two-way communication, can overcome obstacles and meet the needs of Palu’s community, although excessive image-building may reduce voter rationality.